The Proyeksi Permintaan Suplai Energi Listrik Tahun 2018-2038 di Provinsi Papua: Proyeksi Permintaan Suplai Energi Listrik Tahun 2018-2038 di Provinsi Papua - Bonay, Alan Hofni Putra (ReTII, 2019)
In the modern era, it will be very difficult for humans to carry out activities without the presence of electrical energy. This is due to the fact that most of the current human needs are based on the use of electronic instruments and machines that require electrical power as their main source of energy. In addition, the availability of electricity is one of the important parameters for the progress, growth and development of an area in the economic, industrial, public service, commercial sectors and even improve the quality of life of it’s people. So that electrical energy planning is needed to overcome and provide solutions to electrical energy problems. This research uses LEAP (Long-Range Energy Alternative Planning Systems) software with the DKL 3.2 approach model to calculate the projected electricity supply needs in Papua province in 2018-2038. From the calculation results of the projection using the DKL 3.2 method for the needs and customers of electricity in 2018-2038, the demand for electricity in the household, industrial, business, and public sectors grew by 12.66%, 16.43%, 5.87 % and 9.78%. As for the projected number of electricity customers in the same sector, customer growth was 6.42%, 4.50%, 3.40% and 6.42%. The results of this study indicate an increase in energy demand in all customer sectors. Keywords : projection, electrical energy, DKL 3.2 metdod, LEAP